Morphological differentiation across the invasive range in Senecio madagascariensis populations - Dematteis, Bruno (2020)
Invasive species are characterized by their ability to colonize new habitats and establish populations away from their native range. In this sense, these plants are expected to have plastic responses to adapt to the environmental pressures during the invasion process. Hence, the role of natural selection is essential because it might favor the occurrence of advantageous traits. However, gene flow can counteract natural selection because immigrants introduce genes adapted to different conditions, with these introductions tending to homogenize allelic frequencies. In this work, we explore the effect of natural selection in invasive populations of S. madagascariensis in Argentina. We quantified leaf area, head number, and length of internodes and inflorescence from material spanning 54 years (1962–2016) and then compared between the edge versus established ranges. Our results show differences in all the measured plant traits among the sampled areas. However, only leaf area was statistically significant, which evidences different responses under the same environmental pressures in the areas located in the edge and established ranges. On the other hand, unlike homogeneous areas, the areas characterized by phenotypically diverse individuals were related to higher dispersal ability. In this sense, long-distance dispersal between neighboring areas may have had an important role in the recorded values. Furthermore, the implications of natural selection and founder effect in the invasion of S. madagascariensis are discussed.